2016
DOI: 10.1002/2016gl068798
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impact on the roles of temperature and precipitation in western U.S. snowpack variability

Abstract: We employ dynamical downscaling and pseudo global warming methodologies to evaluate climate change impact on the roles of temperature and precipitation in spring snowpack (S) variability across the western United States (U.S.). The negative correlation between S and temperature weakens linearly with elevation, whereas the correlation between S and precipitation increases asymptotically with elevation. The curvilinear relationship in the latter case was not visible in prior studies because of the observation ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 38 publications
3
69
3
Order By: Relevance
“…The projected climate results are consistent with other studies such as the climate projection for the Rocky Mountain headwaters of Colorado River (Christensen et al ; Ray et al ). The results of these downscaled climate projections in the State of Utah and the Jordan River basin are also reported in other studies (Scalzitti et al 2016a, b; Strong et al ; Khatri et al ).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The projected climate results are consistent with other studies such as the climate projection for the Rocky Mountain headwaters of Colorado River (Christensen et al ; Ray et al ). The results of these downscaled climate projections in the State of Utah and the Jordan River basin are also reported in other studies (Scalzitti et al 2016a, b; Strong et al ; Khatri et al ).…”
Section: Resultssupporting
confidence: 84%
“…The statistical downscaling (Reclamation ) was based on more than 20 global climate models forced by four greenhouse gas emission scenarios, referred to as Representative Concentration Pathways (RCPs; Vuuren et al ). For the dynamical downscaling, the high computational expense of our regional climate model configuration (Scalzitti et al 2016a, b) limited the simulation to a mid‐century decade (2035–2044) and a late‐century decade (2085–2094), both under the moderate greenhouse gas emission scenario RCP6.0. For consistency, we focus on climate inputs for the same two decades in the statistical downscaling archive.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, several local studies demonstrated that there is a threshold elevation in mountains, below which temperature is the main controlling factor for snowpack properties, whereas above which precipitation plays a dominant role. The threshold altitude is, for example, 1,400 ± 200 m in a Swiss mountainous area where the station elevation ranges from 316 to 2,690 m (Morán‐Tejeda, López‐Moreno, & Beniston, ), 1,560 ± 120 m in the middle of the Rockie Mountains where the station elevation ranges from 1,295 to 2,256 m (Sospedra‐Alfonso, Melton, & Merryfield, ), and 1,580–2,181 m in six mountains of the western United States where the station elevation ranges from 1,020 to 3,501 m (Scalzittl, Strong, & Kochanski, ). All the above local studies showed that temperature has a negative correlation to snowpack whereas precipitation has a positive correlation.…”
Section: Introductionmentioning
confidence: 99%
“…Even allowing for upslope migration, the rate of changing temperatures may be fast enough that species with long regeneration times like bristlecone pine are unable to migrate fast enough to avoid local extirpation (Aitken et al., ; Loarie et al., ; Neilson et al., ; Van de Ven, Weiss, & Ernst, ). Minimum temperatures in the western Great Basin have increased an average of 1°C between 1910 and 2013 (Millar et al., ), and regional temperatures are expected to rise an additional 2–4°C by the late 21st century (Scalzitti, Strong, & Kochanski, ). Aside from the rate of climate warming, bristlecone pine may also be exposed to greater interspecific competition from other tree species, especially the better‐dispersing limber pine, which could establish rapidly in newly available habitat at and above the current treeline.…”
Section: Introductionmentioning
confidence: 99%